1998
DOI: 10.1046/j.1365-2257.1998.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2 microglobulin and lactate dehydrogenase levels are useful prognostic markers in early stage primary gastric lymphoma

Abstract: The optimal management of primary gastric lymphoma (PGL) remains undecided because a definitive classification for therapeutic decision is not available. The International Index Project has proved to be useful in patients with nodal disease, but in extranodal presentation it has not been tested. We reviewed 297 patients with early stage PGL. They were initially classified according to the prognostic features of the International Index Project. No influence on duration of time to treatment failure (TTF) or over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In PG-DLBCL at early stage, international project index appears to be of no use, because 95% of patients are at low- or low-intermediate risks, and these patients have a good prognosis, but as mentioned, 20–35% could relapse. Previously, we report that elevated serum levels of LDH and B2M can indicate a worse prognosis in this setting of patients, 17 and in a revision of a large number of patients, we can confirm these findings. 3,16 Thus, a different therapeutic approach will be considered to improve the outcome in these patients.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In PG-DLBCL at early stage, international project index appears to be of no use, because 95% of patients are at low- or low-intermediate risks, and these patients have a good prognosis, but as mentioned, 20–35% could relapse. Previously, we report that elevated serum levels of LDH and B2M can indicate a worse prognosis in this setting of patients, 17 and in a revision of a large number of patients, we can confirm these findings. 3,16 Thus, a different therapeutic approach will be considered to improve the outcome in these patients.…”
Section: Discussionsupporting
confidence: 75%
“…16 Some years ago, we performed a retrospective clinical study and found that patients with elevated serum levels of lactic dehydrogenase (LDH) and beta 2 microglobulin (B2M) (>2 of normal levels) have a worse prognosis, independent of other prognostic factors. 17 The treatment of patients with nodal diffuse large B-cell lymphoma (DLBCL) and worse prognosis includes different approaches, more aggressive combinations, including stem cell transplant, or new molecules. Dose-dense chemotherapy, which increases the doseintensity search to eliminate more tumor cells, decreases the possibility that residual cells will be the cause of relapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPI has been considered an excellent prognostic index for patients with diffuse large B cell lymphoma with nodal presentation [9], but in other clinico-pathological conditions, it has not been confirmed. In primary gastric lymphoma, MALT or no-MALT, IPI can not predict outcome, and only DHL and B2M appear to be useful markers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Taking in consideration that PGL appear to be limited to the stomach (stage I and II), initial treatment were surgery and radiotherapy; however, relapse were higher, and actually only in selected cases: bleeding, perforation, bad clinical conditions, those therapeutic approaches are employed chemotherapy, CHOP (cyclophosphamide, doxorubicin, vincristine and Prednisone): was considered the gold standard in PGL an early stage: with a complete response of 85 to 93 % of cases, but, even in patients with good prognosis factors at diagnostic, < 60 years old, limited anatomical site, low or low-intermediate clinical risk according to the International Project Index IPI), good performance status (< 1), and small number of patients could have a worse prognosis and have high-risk of relapse, that while can be refractory to salvages, including stem cell transplant [4]. Some years ago, we found that patients with high of lactic dehydrogenase (LDH) and beta 2 microbuline are associated with a worse prognosis in PGL [5]. Thus, we developed an intensive regimen, that increase doses of cyclophosphamide, and doxorubicin, diminished the interval between cycles of 14 instead of 21 days, that achieve good response rate and outcome [6].…”
Section: Introductionmentioning
confidence: 99%